2008
DOI: 10.28945/198
|View full text |Cite
|
Sign up to set email alerts
|

Enabling a Comprehensive Teaching Strategy: Video Lectures

Abstract: This study empirically tests the feasibility and effectiveness of video lectures as a form of video instruction that enables a comprehensive teaching strategy used throughout a traditional classroom course. It examines student use patterns and the videos' effects on student learning, using qualitative and nonparametric statistical analyses of survey responses and student grades. Groups of student course grades are compared with and without video lectures available.Video lectures are CD and web viewable files t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Similarly, Brecht and Ogilby (2008) found 68.5% of research participants (students) considered that they understand information better through videos. Moreover, Brecht and Ogilby (2008) further argued that a potential benefit of video is that students can have additional processing time to understand the teaching materials. Wang (2016) further indicated that videos are associated with higher learner motivation.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, Brecht and Ogilby (2008) found 68.5% of research participants (students) considered that they understand information better through videos. Moreover, Brecht and Ogilby (2008) further argued that a potential benefit of video is that students can have additional processing time to understand the teaching materials. Wang (2016) further indicated that videos are associated with higher learner motivation.…”
Section: Introductionmentioning
confidence: 91%
“…This suggestion was echoed by the findings of Boateng et al (2016) in which more than half of the participated students in the research considered that videos provide a better and deeper understanding of the learning materials and in an easier way. Similarly, Brecht and Ogilby (2008) found 68.5% of research participants (students) considered that they understand information better through videos. Moreover, Brecht and Ogilby (2008) further argued that a potential benefit of video is that students can have additional processing time to understand the teaching materials.…”
Section: Introductionmentioning
confidence: 91%
“…The use of 'flipped' classrooms has been studied extensively (O'Flaherty and Philips 2015), but there have been fewer studies specifically on the use of video lectures as a medium for delivering programme content, or on the preferences HEI students have when receiving programme content in video form. A study on attitudes towards video lectures and their impact on programme performance by Brecht and Ogilby (2008) found that compared to traditional formats, video lectures improved perceived understanding of content, preparation for exams and preparation for formative assessment. Furthermore, compared to a control group, where video lectures were not available, Brecht and Ogilby (2008) found that pass rates were significantly improved for students who had access to video lectures.…”
Section: Introductionmentioning
confidence: 99%
“…A study on attitudes towards video lectures and their impact on programme performance by Brecht and Ogilby (2008) found that compared to traditional formats, video lectures improved perceived understanding of content, preparation for exams and preparation for formative assessment. Furthermore, compared to a control group, where video lectures were not available, Brecht and Ogilby (2008) found that pass rates were significantly improved for students who had access to video lectures. Giannakos, Jaccheri, and Krogstie (2016) found that video lectures can enhance the perceived value of teaching and learning, particularly at advanced levels.…”
Section: Introductionmentioning
confidence: 99%
“…Video is superior for learning complex skills, as it can expose learners to events that cannot be easily demonstrated (Overbaugh, 1995). Zhang et al (2006, p. 17) hold the view that “video allows students to view actual objects and realistic scenes, to see sequences in motion, and to listen to narration.” Teachers can present, teach and internalize information by using video lectures (Brecht and Ogilby, 2008). Such lectures are also excellent venues for focusing the students’ attention on specific details based on the prepared material itself.…”
Section: Introductionmentioning
confidence: 99%